Anti-Arthritic Activity of Schistosoma mansoni and Trichinella spiralis Derived-Antigens in Adjuvant Arthritis in Rats: Role of FOXP3+ Treg Cells - Eissa, Maha M. (Public Library of Science, 2016)
A growing body of evidence supports the concept of helminths therapy in a variety of autoimmune diseases. Here, we aimed to investigate the protective effects of autoclaved Schistosoma mansoni antigen (ASMA) and Trichinella spiralis antigen (ATSA) on the clinical and immunopathological features of rheumatoid arthritis (RA). Adjuvant arthritis was induced by subcutaneous and intradermal injections of complete Freund’s adjuvant into the plantar surface of the right hind paw and the root of the tail, respectively. Rats were randomly assigned to serve as normal control, untreated arthritis, ASMA or ATSA-treated arthritis groups. Antigens were given by intradermal injection in two doses, two weeks apart. The development, progression of arthritic features, and the impact on animals’ gait and body weight were followed up for 4 weeks. The associated changes in serum cytokines (IL-17, IFN-γ and IL-10), joints’ histopathology and immunohistochemistry of Foxp3+ T regulatory cells (Tregs) were evaluated at the end of the study. Treatment with either ASMA or ATSA attenuated the progression of clinical features of polyarthritis, improved gait and body weight gain, reduced the elevated serum IL-17 and further increased both IFN-γ and IL-10. Histopathologically, this was associated with a remarkable regression of paws’ inflammation that was limited only to the subcutaneous tissue, and a significant increase in the number of Foxp 3+ cells versus the untreated arthritis group. In conclusion, both Schistosoma mansoni and Trichinella spiralis derived antigens exerted protective effect against adjuvant arthritis with better effect achieved by ASMA treatment. This anti-arthritic activity is attributed to upregulation of the Foxp3+ Tregs, with subsequent favorable modulation of both pro- and anti-inflammatory cytokines. The use of autoclaved parasitic antigens excludes the deleterious effects of imposing helminthic infection by using live parasites, which may pave the way to a new therapeutic modality in treating RA.